Sensory Inhibition and Tinnitus: Measurement of Auditory Gating - Morse, Kenneth; Campbell, Julia; Ralston, Lauren (Seminars in Hearing, 2024)
Tinnitus is the perception of sound without the presence of an external stimulus. The mechanisms associated with tinnitus are not entirely known, making diagnosis and treatment challenging. Although tinnitus mechanisms are not entirely known, there is evidence supporting an association between tinnitus with cochlear damage, reduced inhibition, and atypical cortical function. These mechanisms have been studied in animal models and people with tinnitus using a variety of different approaches. One approach that is a possible indicator of tinnitus in humans is sensory or auditory gating, which is a measure of inhibition. The goals of this article are to (1) review the mechanistic evidence associating tinnitus with cochlear damage and reduced inhibition, (2) discuss evidence of inhibitory impairments in people with tinnitus represented by auditory gating, and (3) address potential future directions to improve our ability to evaluate auditory gating mechanisms in people with tinnitus.
Keywords: tinnitus; sensory gating; auditory gating; inhibition